The Model of Innovation Management of Private Hospital in Nakhon Pathom Province - Prasertsak, Anuthida; Piriyapongrat, Paradee; Trakoolchokumnuay, Kttipong (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to study 1) opinion level towards innovation management of private hospitals in Nakhon Pathom Province, and 2) the components of Innovation Management of Private Hospitals in Nakhon Pathom Province. The participants were collected from 165 of medical staff from private hospitals by using simple random sampling.The research instrument used a-5 rating scale with the reliability score of alpha coefficient at 0.98. The statistical data analysis were frequency, percentage, mean, standard deviation and confirmatory factor analysis (CFA). The research findings found that the opinion level towards the innovation management model of private hospitals in Nakhon Pathom province was at the highest level. And the components of innovation management are: 1) the innovation input 2) the innovation process 3) the innovation output and 4) innovation external organization. The results of the structural validity test of innovation management of private hospitals in Nakhon Pathom Province model showed that Chi-square (χ2)=199.012, df=196, χ2/df (CMIN/DF)=1.015, RMR=.016, RMSEA=.000, GFI=.915, AGFI=.880, and CFI=0.999. Based on the findings, it indicated that innovation management of private hospitals in Nakhon Pathom Province model was consistent with empirical data significantly. As a result, private hospital administrators should prioritize developing the innovation process both inside and outside organizations and encourage personnel to develop and create innovations that are useful and can be applied in practice.